JAPANESE ENCEPHALITIS - Nur Ika Hariastuti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2012)
Japanese encephalitis is a vector-borne disease caused by a virus. The disease is common in children and can cause inflammation of the brain. In Indonesia the disease is consider as a neglected disease, although some studies suggest Japanese encephalitis infections in both animals and humans in some regions. Transmission cycle actually happens between mosquitoes with the host such as pigs or birds. Transmission to humans occurs only incidentally. Disease diagnosis in humans can be done by rapid test, ELISA, or PCR. While control using a vaccine is not a program yet in Indonesia